1995
DOI: 10.1063/1.359186
|View full text |Cite
|
Sign up to set email alerts
|

Flicker noise in submicron metal oxide semiconductor field effect transistors with nitrided gate oxide

Abstract: Effects of the gate dielectric nitridation on the flicker (1/f) noise characteristics of submicron metal oxide semiconductor field effect transistors (MOSFETs) are reported. Low-frequency (1/f) noise measurements on nitrided and non-nitrided gate oxide MOSFETs of the same geometry have been carried out, showing different noise behavior with respect to the flicker noise amplitude and bias dependence. It is found that gate oxide nitridation not only increases the flicker noise amplitude, but also enhances the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…This shows that the nitridation of the interface may have an additional impact on the stoichiometry of the interfacial layer by creating a high density of N-related noisy traps close to the Si-SiO 2 interface. 6,[13][14][15][16] Relation between nitrogen related defects, oxygen vacancies, and the impact of 1/f noise in nitrided-interface and non-nitridedinterface n-MOSFETs.-Depending on the ambient during PDA and the use of DPN, it is clear that different amounts ͑and profiles͒ of nitrogen will be introduced in the gate stack, which may influence the density and profiles of the N-and oxygen-vacancy-related traps. These concentration profiles are also important to determine the impact on 1/f noise.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This shows that the nitridation of the interface may have an additional impact on the stoichiometry of the interfacial layer by creating a high density of N-related noisy traps close to the Si-SiO 2 interface. 6,[13][14][15][16] Relation between nitrogen related defects, oxygen vacancies, and the impact of 1/f noise in nitrided-interface and non-nitridedinterface n-MOSFETs.-Depending on the ambient during PDA and the use of DPN, it is clear that different amounts ͑and profiles͒ of nitrogen will be introduced in the gate stack, which may influence the density and profiles of the N-and oxygen-vacancy-related traps. These concentration profiles are also important to determine the impact on 1/f noise.…”
Section: Discussionmentioning
confidence: 99%
“…While all PDAs yield similar S VG values and similar variation with gate voltage overdrive, an order of magnitude lowering occurs for the non-nitrided and no-anneal condition, indicating the presence of nitrogen-related "noisy" traps. 6,[13][14][15][16] From the above results, it is clear that ͑i͒ nitridation of the interface has an impact on both the noise magnitude and the noise mechanism in these devices, ͑ii͒ nitridation of the interface suppresses the effect of the postdeposition anneal, and ͑iii͒ interface nitridation with no anneal has a different noise behavior when compared to a nitrided interface and postdeposition anneal conditions.…”
Section: G820mentioning
confidence: 90%
See 1 more Smart Citation
“…The trap density derived for the p-channel MuGFETs is about 2 times higher than for the corresponding n-type devices. The impact of nitridation of the SiO 2 gate oxide on the LF noise has been studied extensively (21)(22)(23)(24)(25)(26). It has been shown that the presence of nitrogen introduces amphoteric traps in the gate oxide, which increases the 1/f noise.…”
Section: Discussionmentioning
confidence: 99%
“…It was found for SiO 2 oxides, that nitridation provides resistance against interface state generation under stress, insensitivity to radiation and improved dopant barrier properties. Nitridation is also found to decrease gate leakage current but reduces mobility [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 96%